In Vitro Modeling of Skin Barrier Disruption and its Recovery by Ceramide-Based Formulations - Čuříková-Kindlová, Barbora Amélie; Vovesná, Aneta; Nováčková, Anna; Zbytovská, Jarmila (AAPS PharmSciTech, 2021)
Disrupted skin barrier, one of the severe attributes of inflammatory skin diseases, is caused by lower content and pathological changes of lipids in the uppermost skin layer-stratum corneum (SC). Restoring skin barrier with native skin lipids, especially ceramides (Cers), appears to be a promising therapy with minimum side effects. For testing the efficiency of these formulations, suitable in vitro models of the skin with disrupted barriers are needed. For the similarity with the human tissue, our models were based on the pig ear skin. Three different ways of skin barrier disruption were tested and compared: tape stripping, lipid extraction with organic solvents, and barrier disruption by sodium lauryl sulfate. The level of barrier disruption was investigated by permeation studies, and parameters of each method were modified to reach significant changes between the non-disrupted skin and our model. Fourier transform infrared (FTIR) spectroscopy was employed to elucidate the changes of the skin permeability on the molecular scale. Further, the potential of the developed models to be restored by skin barrier repairing agents was evaluated by the same techniques. We observed a significant decrease in permeation characteristics through our in vitro models treated with the lipid mixtures compared to the untreated damaged skin, which implied that the skin barrier was substantially restored. Taken together, the results suggest that our in vitro models are suitable for the screening of potential barrier repairing agents.
Keywords: lipidy; epidermis; ceramides; liposomes; FTIR spectroscopy; permeation experiment; Animals; kůže; ceramidy; Skin; stratum corneum lipids; Swine; Permeability; Lipids; zvířata; prasata; skin barrier disruption models; Ceramides; permeabilita; Epidermis; topical treatment